Relationship between regional myocardial oxygenation and perfusion in patients with coronary artery disease: insights from cardiovascular magnetic resonance and positron emission tomography. - Karamitsos, T; Leccisotti, L; Arnold, JR; Recio-Mayoral, A; Bhamra-Ariza, P; Howells, R; Searle, N; Robson, M; Rimoldi, O; Camici, P; Neubauer, S; Selvanayagam, J (2010)
BACKGROUND: It is recognized that the interplay between myocardial ischemia, perfusion, and oxygenation in the setting of coronary artery disease (CAD) is complex and that myocardial oxygenation and perfusion may become dissociated. Blood oxygen level-dependent (BOLD) cardiovascular magnetic resonance (CMR) has the potential to noninvasively measure myocardial oxygenation, whereas positron emission tomography (PET) with oxygen-15 labeled water is the gold standard technique for myocardial blood flow quantification. Thus, we sought to apply BOLD CMR at 3 T and oxygen-15-labeled water PET in patients with CAD and normal volunteers to better understand the relationship between regional myocardial oxygenation and blood flow during vasodilator stress. METHODS AND RESULTS: Twenty-two patients (age, 62+/-8 years; 16 men) with CAD (at least 1 stenosis > or =50% on quantitative coronary angiography) and 10 normal volunteers (age, 58+/-6 years; 6 men) underwent 3-T BOLD CMR and PET. For BOLD CMR, 4 to 6 midventricular short-axis images were acquired at rest and during adenosine stress (140 microg/kg/min). Using PET with oxygen-15-labeled water, myocardial blood flow was measured at baseline and during adenosine in the same slices. BOLD images were divided into 6 segments, and mean signal intensities calculated. Taking > or =50% stenosis on quantitative coronary angiography as the gold standard, cutoff values for stress myocardial blood flow (<2.45 mL/min/g; AUC, 0.83) and BOLD signal intensity change (<3.74%; AUC, 0.78) were determined to define ischemic segments. BOLD CMR and PET agreed on the presence or absence of ischemia in 18 of the 22 patients (82%) and in all normal subjects. On a per-segment analysis, 40% of myocardial segments with stress myocardial blood flow below the cutoff of 2.45 mL/min/g did not show deoxygenation, whereas 88% of segments with normal perfusion also had normal oxygenation measurements. CONCLUSIONS: Regional myocardial perfusion and oxygenation may be dissociated, indicating that in patients with CAD, reduced perfusion does not always lead to deoxygenation.